2021
DOI: 10.3390/cells10081922
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Associates of Soft Scale Insects (Coccomorpha: Coccidae)

Abstract: Ophiocordyceps fungi are commonly known as virulent, specialized entomopathogens; however, recent studies indicate that fungi belonging to the Ophiocordycypitaceae family may also reside in symbiotic interaction with their host insect. In this paper, we demonstrate that Ophiocordyceps fungi may be obligatory symbionts of sap-sucking hemipterans. We investigated the symbiotic systems of eight Polish species of scale insects of Coccidae family: Parthenolecanium corni, Parthenolecanium fletcheri, Parthenolecanium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…We infer that the strong signal of insect sources in the FEAST analysis is not primarily due to vertical transmission, which should lead to more homogenous and less diverse communities than we observe here [56]. Although our understanding of vertical transmission from parent to offspring among insects has been primarily derived from studies of bacterial symbionts [57][58][59][60][61], vertical transmission of fungal symbionts in insects does occur [56,[62][63][64]. Transovarial transmission was recently demonstrated as a mechanism for Ophiocordyceps fungal symbionts of scale insects [63], as well as for the microsporidian pathogen Nosema bombycis in the related tobacco cutworm pest Spodoptera litura [65].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We infer that the strong signal of insect sources in the FEAST analysis is not primarily due to vertical transmission, which should lead to more homogenous and less diverse communities than we observe here [56]. Although our understanding of vertical transmission from parent to offspring among insects has been primarily derived from studies of bacterial symbionts [57][58][59][60][61], vertical transmission of fungal symbionts in insects does occur [56,[62][63][64]. Transovarial transmission was recently demonstrated as a mechanism for Ophiocordyceps fungal symbionts of scale insects [63], as well as for the microsporidian pathogen Nosema bombycis in the related tobacco cutworm pest Spodoptera litura [65].…”
Section: Discussionmentioning
confidence: 96%
“…Although our understanding of vertical transmission from parent to offspring among insects has been primarily derived from studies of bacterial symbionts [57][58][59][60][61], vertical transmission of fungal symbionts in insects does occur [56,[62][63][64]. Transovarial transmission was recently demonstrated as a mechanism for Ophiocordyceps fungal symbionts of scale insects [63], as well as for the microsporidian pathogen Nosema bombycis in the related tobacco cutworm pest Spodoptera litura [65]. Although S. frugiperda may harbor a few taxa that are vertically transmitted, perhaps those we identify as core, and shared across a majority of insects sampled (Table S1), we infer that the strong source contribution of conspecific insects found by FEAST is more likely due to horizontal transmission, the acquisition of microbial symbionts from other insects or from shared environmental sources.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is very likely that the transcripts and reads assigned to the family Ophiocordycipitaceae in all our libraries belonged to S. titanus YLSs that were experimentally characterized. In this context, it is notable that also fungal endosymbionts of cicadas (Matsuura et al, 2018 ), leafhoppers (Nishino et al, 2016 ; Kobiałka et al, 2018 ), aphids (Vogel and Moran, 2013 ), scale insects (Podsiadło et al, 2018 ; Szklarzewicz et al, 2021 ), and planthoppers (Suh et al, 2001 ) appeared to be phylogenetically related to the genus Ophiocordyceps .…”
Section: Discussionmentioning
confidence: 99%
“…Coccoids are plant sap-sucking hemipterans that are considered serious pests in agriculture, horticulture, and forestry [ 2 ]. Szklarzewicz and coauthors [ 2 ] investigated the symbiotic systems of eight Polish species of scale insects of the Coccidae family: Parthenolecanium corni , Parthenolecanium fletcheri , Parthenolecanium pomeranicum , Psilococcus ruber , Sphaerolecanium prunasti , Eriopeltis festucae , Lecanopsis formicarum and Eulecanium tiliae . The histological, ultrastructural and molecular analyses showed that all these species host fungal symbionts in fat body cells.…”
mentioning
confidence: 99%
“…Ophiocordyceps fungi are commonly known as virulent, specialized entomopathogens. The essential role of the fungal symbionts observed in the biology of the soft scale insects examined was confirmed by their transovarial transmission between generations [ 2 ].…”
mentioning
confidence: 99%